Compositional analysis of semolina with added fibers by near infrared spectroscopy (NIR) - Morimitsu, Fernanda Lie; Barbin, Douglas Fernandes; Badaró, Amanda Teixeira; Ferreira, Amanda Rios; Clerici, Maria Teresa Pedrosa Silva (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Fiber addition to semolina is important to promote better health, since fibers help to prevent chronical diseases such as obesity and diabetes. Since traditional methods for fiber determination are slow and demand sample preparation, the development of less invasive techniques is necessary. Therefore, near infrared spectroscopy (NIR) was used as a fast and non-destructive method to identify fibers added to semolina.